Missed Paracetamol (Acetaminophen) Overdose Due to Confusion Regarding Drug Names - G. Hewett, David; Shields, Jennifer; Stephen Waring, W. (Current Drug Safety, 2013)
Immediate management of drug overdose relies upon the patient account of what was ingested and how much. Paracetamol (acetaminophen) is involved in around 40% of intentional overdose episodes, and remains the leading cause of acute liver failure in many countries including the United Kingdom. In recent years, consumers have had increasing access to medications supplied by international retailers via the internet, which may have different proprietary or generic names than in the country of purchase. We describe a patient that presented to hospital after intentional overdose involving ‘acetaminophen’ purchased via the internet. The patient had difficulty recalling the drug name, which was inadvertently attributed to ‘Advil’, a proprietary non-steroidal anti-inflammatory drug. The error was later recognised when the drug packaging became available, but the diagnosis of paracetamol overdose and initiation of acetylcysteine antidote were delayed. This case illustrates the benefit of routinely measuring paracetamol concentrations in all patients with suspected poisoning, although this is not universally accepted in practice. Moreover, it highlights the importance of the internet as a source of medications for intentional overdose, and emphasises the need for harmonisation of international drug names to improve patient safety.
Keywords: drug name